Epidemiological Study of Two Wheeler Accident Victims In Rural South India - Reddy, Ananda; Balaraman , R (Journal of Indian Academy of Forensic Medicine, 2016)
Vehicular accidents are steadily mounting up on the Indian roads, so critical analysis of causative  factors is pivotal to prevent them in future. This study was designed to assess the epidemiological factors  constrained in two wheeler accident victims. It’s a cross-sectional study of two wheeler related deaths  autopsied at the IGGGH & PGI in Pudducherry. Data gathered by interviews, autopsy and results were  analysed. Two wheeler crashes were accountable for 10.85% of all 1318autopsies. Most vulnerable are  males (81%) and individuals between 16-29 years (35%). Most victims were from rural area (47%),  Hindus (79%), married (49%) and middle income (62%) group. These fatal events frequent on national  highways (36%), evening rush traffic hours (42%) and involves motorcycle occupants (64%) and  pedestrians (24%). Prime RTA contributors like human errors; vehicle and road factors were evaluated.  Importing awareness and education among vulnerable population alleviate the frequency of accidents  and dreaded outcomes.
Keywords: Two wheeler accidents; Fatalities; Motorcycles; Human errors